Associations between different forms of peer victimization and school absences: The moderating role of teacher attachment and perceived school safety. Issue 1 (24th October 2020) - Williford, Anne; Fite, Paula; Diaz, Kathleen; Singh, Mehar
Abstract: Given the significant negative impacts of peer victimization on youth development, studies have sought to understand what buffers against these consequences. To that end, the present study examined whether teacher attachment and perceptions of school safety moderated the associations between different forms of victimization and school absences over the course of an academic year among a sample of 272 high school students. Findings indicated that teacher attachment moderated the associations between relational and cyber victimization and absences, while perceived school safety moderated associations between relational victimization and absences. However, findings pertaining to cyber victimization were not as anticipated. Implications for prevention and intervention efforts in high schools are discussed.